Interplay Between BALL and CREB Binding Protein Maintains H3K27 Acetylation on Active Genes in Drosophila - Shaukat, Ammad; Khan, Muhammad Haider Farooq; Ahmad, Hina; Umer, Zain; Tariq, Muhammad (Frontiers in Cell and Developmental Biology, 2021)
CREB binding protein (CBP) is a multifunctional transcriptional co-activator that interacts with a variety of transcription factors and acts as a histone acetyltransferase. In Drosophila, CBP mediated acetylation of histone H3 lysine 27 (H3K27ac) is a known hallmark of gene activation regulated by trithorax group proteins (trxG). Recently, we have shown that a histone kinase Ballchen (BALL) substantially co-localizes with H3K27ac at trxG target loci and is required to maintain gene activation in Drosophila. Here, we report a previously unknown interaction between BALL and CBP, which positively regulates H3K27ac. Analysis of genome-wide binding profile of BALL and CBP reveals major overlap and their co-localization at actively transcribed genes. We show that BALL biochemically interacts with CBP and depletion of BALL results in drastic reduction in H3K27ac. Together, these results demonstrate a previously unknown synergy between BALL and CBP and reveals a potentially new pathway required to maintain gene activation during development.